(untitled) (Bangladesh Journal of Plant Taxonomy, 2010)
Not available. Keywords: Monodictys putredinis; new records; Stachybotrys atra. DOI: 10.3329/bjpt.v17i1.5397 Bangladesh J. Plant Taxon. 17(1): 101-103, 2010 (June)